Impact of a multimodal treatment of auricular keloids on the patient’s health-related quality of life: a prospective study - Helmer, Alexander; Cantillo, Marcio; Zaubitzer, Lena; Kramer, Benedikt Alexander; Rottery, Nicole; Sadick, Haneen; Häussler, Daniel (ENT, 2025)
Introduction: Auricular keloids may be associated with social stigma and impair patients’ quality of life (QoL) significantly. Little is known about the effect ...
Gesehen am 30.09.2025